Can Medical Herbs Stimulate Regeneration or Neuroprotection and Treat Neuropathic Pain in Chemotherapy-Induced Peripheral Neuropathy?. (30th July 2013) - Schröder, Sven; Beckmann, Kathrin; Franconi, Giovanna; Meyer-Hamme, Gesa; Friedemann, Thomas; Greten, Henry Johannes; Rostock, Matthias; Efferth, Thomas
Abstract : Chemotherapy-induced neuropathy (CIPN) has a relevant impact on the quality of life of cancer patients. There are no curative conventional treatments, so further options have to be investigated. We conducted a systematic review in English and Chinese language databases to illuminate the role of medical herbs. 26 relevant studies on 5 single herbs, one extract, one receptor-agonist, and 8 combinations of herbs were identified focusing on the single herbs Acorus calamus rhizoma, Cannabis sativa fructus, Chamomilla matricaria, Ginkgo biloba, Salvia officinalis, Sweet bee venom, Fritillaria cirrhosae bulbus, and the herbal combinations Bu Yang Huan Wu, modified Bu Yang Huan Wu plus Liuwei Di Huang, modified Chai Hu Long Gu Mu Li Wan, Geranii herba plus Aconiti lateralis praeparata radix, Niu Che Sen Qi Wan (Goshajinkigan), Gui Zhi Jia Shu Fu Tang (Keishikajutsubuto), Huang Qi Wu Wu Tang (Ogikeishigomotsuto), and Shao Yao Gan Cao Tang (Shakuyakukanzoto) . The knowledge of mechanism of action is still limited, the quality of clinical trials needs further improvement, and studies have not yielded enough evidence to establish a standard practice, but a lot of promising substances have been identified. While CIPN has multiple mechanisms of neuronal degeneration, a combination of herbs or substances might deal with multiple targets for the aim of neuroprotection or neuroregeneration in CIPN.